Discrete universality theorem for Matsumoto zeta-functions and nontrivial zeros of the Riemann zeta-function - Nakai, Keita (Mathematical Modelling and Analysis, 2025)
In 2017, Garunkštis, Laurinčikas and Macaitienė proved the discrete universality theorem for the Riemann zeta-function shifted by imaginary parts of nontrivial zeros of the Riemann zeta-function. This discrete universality has been extended to various zeta-functions and L-functions. In this paper, we generalize this discrete universality for Matsumoto zeta-functions.